1983
DOI: 10.1007/bf00334831
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a DNA sequence related to several plasmids from Bacillus thuringiensis after a mating involving the Streptococcus faecalis plasmid pAMβ1

Abstract: The transmissible plasmid pAM beta 1, which codes for resistance to erythromycin and lincomycin, was transferred from Streptococcus faecalis to several strains of Bacillus thuringiensis by a filter-mating process. Introduction of pAM beta 1 into the Emr transconjugant strains of B. thuringiensis was confirmed by Southern hybridisation using the 32P-labelled pAM beta 1 as a probe. In the B. thuringiensis transconjugant strains, used as donors, the beta plasmid conserved its ability to be transferred during intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(40 citation statements)
references
References 16 publications
0
40
0
Order By: Relevance
“…The bacterial strains Kpn223 and Kpn555 were strikingly different as recipients, prompting a comparison of the strains. The number of plasmids and type of replicon differed between strains Kpn223 and Kpn555, but the role of the number of recipient plasmids on conjugation efficiency is inconclusive (51)(52)(53). Kpn223 seems to carry only a plasmid with limited presumptive transfer genes and unclear conjugal ability, which may explain, in part, its high-efficiency recipient ability.…”
Section: Discussionmentioning
confidence: 99%
“…The bacterial strains Kpn223 and Kpn555 were strikingly different as recipients, prompting a comparison of the strains. The number of plasmids and type of replicon differed between strains Kpn223 and Kpn555, but the role of the number of recipient plasmids on conjugation efficiency is inconclusive (51)(52)(53). Kpn223 seems to carry only a plasmid with limited presumptive transfer genes and unclear conjugal ability, which may explain, in part, its high-efficiency recipient ability.…”
Section: Discussionmentioning
confidence: 99%
“…There are reports in the literature presenting evidence of repetitive sequences and transposonlike elements present on B. thuringiensis plasmids (18,(20)(21)(22)(23)(24). Therefore, the variant plasmids might result from transposition of sequences from B. thuringiensis plasmids to pXO1.…”
Section: Discussionmentioning
confidence: 99%
“…Studies by Lereclus et al (12,13) have shown that Tn4430 promotes deletions in DNA sequences adjacent to its endpoints. It is possible then that Tn4430 or insertion elements related to IR1 are responsible for the spontaneous loss of DNA sequences on this region of pXO12.…”
Section: Discussionmentioning
confidence: 99%